ANALISIS TINGKAT KEBERHASILAN PANGGILAN MOBILE BTS (BASED TRANSCIEVER STATION) SEBAGAI RECOVERY JARINGAN SELULER PADAT TRAFFIK - Syarif Alqadri . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Mobile BTS can be used for covering busy network, and note B will be affected phone calls so that the customers feel annoyed when make phone calls. Other factors that make busy network traffic are trouble hardware, Coverage is not working efficient, unstable traffic in node B. Based on quality network from analysis CCSR_CS, CCSR_PS and CSSR_CS, CSSR_PS, there is a cell that traffic capacity that’s below KPI standard, so that some phone calls will be disconnect while making connection. Node B museum is decreasing to 89,41 % on value (60939 CCSR CS) that happened on 12st december 2016, this value is decrasing to 0,59%, so that add capacity on node B is needed. Adding capacity for minimizing cost without build new node B. mobile BTS can be used for covering busy network on network celular at that location. The data that has been commisioning on 12st december 2016 get result (60939 CCSR CS) 99,49 %. Good node B is a node B that has KPI PT.Telkomsel standard which accessibility, retainability, and mobility are above 90%. Key words : KPI standard, Network Recovery, Mobile BTS.